MODEL ANTISIPASI KENAKALAN REMAJA DI KOTA KUPANG - Alexander Simon Pally; Daud Yaferson Dollu (BULLET : Jurnal Multidisiplin Ilmu, 2023)
In this study the emphasis on the role of the family and the surrounding environment is a very important aspect of influencing and shaping a child's behavior. Whether or not harmonious and intensive and whether or not the interaction between family members will affect the tendency of children to be naughty. The values that develop and appear in the order of social life are always experienced by children in their lives. The problem that arises is the rapid flow of new values that come through developments in information technology such as television, magazines, newspapers, readings that are easy to get everywhere or the most sophisticated ones such as the internet as if they cannot stop children. The result is being naughty and the desire to oppose old values that have long been established can confuse children, when there are no role models in the community itself. The method of this research is an empirical juridical approach. The Juridical Empirical research method is library law research which is carried out by examining secondary data library materials, then followed by conducting primary data research in the field such as interviews. The researchers then conducted interviews with counseling teachers at SMAN 2 Kota Kupang, Maria, on March 6, 2023.